Muhammadiyah Sebagai Gerakan Pendidikan - Huda, Syamsul; Kusumawati, Dahani (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
The identity of Muhammadiyah as a modern movement cannot be separated from the conceptualization produced in the field of education. The colonial era which is identical with the dichotomy of education and science, began to be reduced by the Muhammadiyah movement that carries scientific integration, a balance between science and religion and also as the concern expression of KH. Ahmad Dahlan towards education. The historicity of Muhammadiyah as an educational movement can be referred to the formulations of the purpose of the Muhammadiyah's presence started from 1921 until 1971 which describe education as the basis for its movements and actions. Muhammadiyah wants to provide a new perspective namely education is holistic integrative, not in a partial dichotomous area, which can contribute to the development and progress of the nation.